Additional volumetric modulated arc therapy to vertebral metastases abutting the previously irradiated site - Takatsugu Kawase; Baku Sakashita; Kazuyoshi Kanai; Minako Uchino; Tomoko Itazawa; Satoshi Nagasaka; Satsuki Kina (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2014)
Introduction: Lung cancer frequently causes metastases to the spine, especially to the thoracic vertebrae, which sometimes compress the spinal cord and induce irreversible palsy. Many patients suffering from metastatic spinal tumors need to undergo repetitive radiotherapy. In such situations, intensity-modulated radiotherapy including volumetric modulated arc therapy can reduce the dose delivered to the spinal cord at the junction.  Case Report: The authors describe a case of thoracic vertebral metastases from lung cancer treated with two courses of radiotherapy. In the second course, volumetric modulated arc therapy was adopted and a columnar-shaped planning target volume with a concave portion was configured.  Conclusion: The authors propose an approach aimed at realizing both junctional safety and the conformality of the spinal column, which may be an option for repetitive irradiation to heterochronic spinal metastases.